Internet information services (IIS) 7.0 : - Stanek, William R. (Microsoft Press, 2008)
Here's the eminently practical, pocket-sized reference for IT and Web professionals working with IIS 7.0. Designed for quick referencing and compulsively readable, this portable guide covers all the basics needed for Web administration fundamentals, Web server administration, essential services administration, and performance, optimization, and maintenance. It s the fast-answers guide that helps users consistently save time and energy as they administer IIS 7.0. Written by an award-winning author of more than two dozen computer books, this guide puts expert administration and troubleshooting advice right at your fingertips.